Rac1‐Rab11‐FIP3 regulatory hub coordinates vesicle traffic with actin remodeling and T‐cell activation. (6th May 2016) - Bouchet, Jérôme; del Río‐Iñiguez, Iratxe; Lasserre, Rémi; Agüera‐Gonzalez, Sonia; Cuche, Céline; Danckaert, Anne; McCaffrey, Mary W; Di Bartolo, Vincenzo; Alcover, Andrés
Abstract: The immunological synapse generation and function is the result of a T‐cell polarization process that depends on the orchestrated action of the actin and microtubule cytoskeleton and of intracellular vesicle traffic. However, how these events are coordinated is ill defined. Since Rab and Rho families of GTPases control intracellular vesicle traffic and cytoskeleton reorganization, respectively, we investigated their possible interplay. We show here that a significant fraction of Rac1 is associated with Rab11‐positive recycling endosomes. Moreover, the Rab11 effector FIP3 controls Rac1 intracellular localization and Rac1 targeting to the immunological synapse. FIP3 regulates, in a Rac1‐dependent manner, key morphological events, like T‐cell spreading and synapse symmetry. Finally, Rab11‐/FIP3‐mediated regulation is necessary for T‐cell activation leading to cytokine production. Therefore, Rac1 endosomal traffic is key to regulate T‐cell activation. Synopsis: Rac1‐mediated actin cytoskeleton rearrangements required for normal T‐cell morphology and activation depend on association of Rac1 with Rab11‐FIP3‐positive recycling endosomes. Rac1 is associated with Rab11‐positive recycling endosomes. Rab11 and its effector protein FIP3 regulate Rac1 subcellular localization, controlling the equilibrium between membrane and endosome associated Rac1. FIP3 silencing disperses Rac1 endosomes in the cytoplasm. Rac1 dispersal leads to altered T‐cell cortical rigidity, T‐cell spreading, and immunological synapse symmetry. FIP3 silencing leads to increased T‐cell activation and cytokine production in a Rac1‐dependent manner. Abstract : Rac1‐mediated actin cytoskeleton rearrangements required for normal T‐cell morphology and activation depend on association of Rac1 with Rab11‐FIP3‐positive recycling endosomes.